Analisis Yuridis Penerapan UU Nomor 12 Tahun 1995 pada Narapidana Narkotika Rutan Batam - Berno Fujiyanto (Journal of Law and Policy Transformation, 2019)
In accordance with Law No. 12 of 1995 concerning correctional facilities, that prisoners have the right to get a reduction in criminal time (remission), get the opportunity to assimilate, get leave before free. However, after the amendment to regulations regarding the conditions for granting prisoners rights contained in Government Regulation No. 99 of 2012, there was a tightening of the conditions for granting rights to prisoners, one of which was a narcotics case. The main problem in this research is why Narcotics Criminal Prisoners in Batam Class IIA Detention Center have difficulty obtaining their rights contained in Article 14 Paragraph 1 of Law No.12 of 1995 concerning Corrections, and what are the factors and constraints for narcotics inmates in Batam Class IIA Detention Center to get their rights.